Mechanisms of change in metacognitive and cognitive behavioral therapy for treatment-resistant anxiety: The role of metacognitive beliefs and coping strategies. Issue 3 (1st August 2018) - Hoffart, Asle; Johnson, Sverre Urnes; Nordahl, Hans Morten; Wells, Adrian
Metacognitive therapy (MCT) has shown promising outcomes across disorders, but, currently, little is known about the mechanisms of change in MCT as well as their specificity compared to those of cognitive behavioral therapy (CBT). The main purpose of this study was to examine the within-person relationships between features of the cognitive attentional syndrome (CAS)—the thinking style supposed to maintain clinical disorders according to the MCT model—and anxiety over the course of MCT and CBT for comorbid anxiety disorders. Seventy-four inpatients had been randomized to either MCT or CBT and actually started treatment. CAS features and anxiety were assessed weekly during treatment. These measures were disaggregated to their within- and between-person components and used as predictors in mixed models. All CAS features—coping activities, negative metacognitive beliefs, and positive metacognitive beliefs—decreased over the course of treatment. Negative and positive beliefs decreased more in MCT than in CBT. Time-specific changes in positive metacognitive beliefs predicted variations in subsequent anxiety across the two treatments (within-person effect). The finding of a within-person relationship between positive metacognitive beliefs and subsequent anxiety has the clinical implication that reduction in these beliefs may be important for treatment response.